High Resolution Discharge Simulations Over Europe and the Baltic Sea Catchment - Hagemann, Stefan; Stacke, Tobias; Ho-Hagemann, Ha T. M. (Frontiers in Earth Science, 2020)
Regional coupled system models require a high-resolution discharge component to couple their atmosphere/land components to the ocean component and to adequately resolve smaller catchments and the day-to-day variability of discharge. As the currently coupled discharge models usually do not fulfill this requirement, we improved a well-established discharge model, the HD model, to be globally applicable at 5 Min. resolution to prepare high-resolution discharge simulations over Europe and the Baltic Sea catchment. Here, no river specific parameter adjustments were conducted so that the model is generally applicable for climate change studies and over ungauged catchments. For the validation of the 5 Min. HD (HD5) model, we drive it with prescribed fields of surface and subsurface runoff. As no large-scale observations of these variables exist, they need to be calculated by a land surface scheme or hydrology model using observed or re-analyzed meteorological data. In order to pay regard to uncertainties introduced by these calculations, three different methods and datasets were used to derive the required fields of surface and subsurface runoff for the forcing of the HD5 model. 10-years simulations (2000-2009) show that for many European rivers, where daily discharge observations were available for comparison, the HD5 model captures the main discharge peaks reasonably well. As direct anthropogenic impact on the discharge, such as by regulation or dams, is not regarded in the HD model, those effects generally cannot be simulated. Thus, discharges for many heavily regulated rivers in Scandinavia or for the rivers Volga and Don are not well represented by the model. The comparison of the simulated discharges obtained indicates that the HD5 model is suitable to evaluate the terrestrial hydrological cycle of climate models or land surface models, especially with regard to the separation of throughfall (rain or snow melt) into surface and subsurface runoff.